Knowledge of Periodontal Diseases, Oral Hygiene Practices, and Self-Reported Periodontal Problems among Pregnant Women and Postnatal Mothers Attending Reproductive and Child Health Clinics in Rural Zambia - T. M. Kabali; E. G. Mumghamba (International Journal of Dentistry)
Aim. To determine the level of knowledge of periodontal diseases, practices regarding oral hygiene, and self-perceived periodontal problems among pregnant and postnatal women attending reproductive and child health clinics in rural districts of Zambia. Methodology. This was a quantitative, questionnaire-based, descriptive, and cross-sectional study that recruited 410 women aged 15 to 43 years. Data were analyzed using SPSS v19.0 computer program. Results. Participants knowledgeable of periodontal diseases were 62%; gingivitis signs included gum swelling (87.4%) and bleeding (93.3%). Of all participants, 95.6% practiced tooth brushing: twice/day (38.5%), using plastic toothbrush (95.6%), chewing stick (12.2%), toothpick (10.7%), dental floss (2.0%), and tongue cleaning (55.4%). Self-reported periodontal problems were bleeding gums (23.2%), gums that were reddish (10.5%), swollen (11.0%), painful (15.9%), and mobile teeth (3.4%). In logistic regression analysis, painful gums, reddish gums, and toothpick use were 21.9, 4.7, and 4.3 respectively, significantly more likely to cause gum bleeding on tooth brushing. Conclusions. Most studied women had general knowledge of periodontal diseases but only few knew the cause. All participants performed tooth cleaning; however, majority did not know appropriate practices, and only few had periodontal problems. Integration of oral health to general health promotion and periodontal therapy to pregnant women at high risk is recommended.